PENGARUH KUALITAS AUDIT DAN KOMPENSASI RUGI FISKAL TERHADAP PENGHINDARAN PAJAK: Studi Kasus Perusahaan Real Estate Dan Properti Di BEI - Panjaitan, Muhammad Adriansyah; Lesmana, Muhammad Taufik (Gapenas Publisher, 2025)
The purpose of this study is to determine the effect of audit quality and fiscal loss compensation on tax avoidance in real estate and property companies on the Indonesia Stock Exchange in 2021-2024 partially and simultaneously. The approach used in this study is an associative approach. The population in the study is real estate and property companies listed on the Indonesia Stock Exchange in 2022-2024. The sampling method used is purposive sampling so that 37 samples were obtained. The total number of data processed in this study for 3 years is 111 data. There are 29 data that need to be outliers due to data abnormalities, so the final sample used in the study is 82 observation data. The data collection technique is using documentation. The data analysis technique in this study is multiple regression. The results of this study indicate that audit quality partially has no significant effect on tax avoidance, with a significance value of 0.621> 0.05. Fiscal loss compensation partially has a significant effect on tax avoidance, with a significance value of 0.009 <0.05. Audit quality and fiscal loss compensation simultaneously have an effect on tax avoidance, with a significance value of 0.025 <0.05